My Museum - Adistana, Natasya (Nanyang Technological University, 2020)
The motivation of this project is to improve personal meaningfulness in museum visit experiences for students in Singapore in order to encourage more visitation to exhibitions administered by National Museum and Heritage institutions under the National Heritage Board. Therefore, My Museum is a mobile application for students as a platform to curate personal meaningfulness in museums in Singapore. Hoping that visiting museums can develop into a habit when one finds personal meaningfulness, the main vision of My Museum is to provide a digital assistance for personalised experiences.